Consumer Legal Protection Against the Distribution of Illicit Cosmetics in North Gorontalo - Rahmatiya Latif; Weny Almoravid Dungga; Sri Nanang M. Kamba (Journal of Law, Human Rights, Immigration, and Corrections, 2026)
The distribution of illicit cosmetic products in North Gorontalo traditional markets poses highly substantial health risks, highlighting a critical gap between statutory consumer protection norms and empirical practices. This study evaluates the efficacy of legal safeguards in ensuring consumer security. Employing an empirical juridical methodology with statutory and conceptual frameworks, this research utilizes field interviews with the Gorontalo BBPOM enforcement team, market traders, and consumers, alongside comprehensive literature reviews. Findings indicate that legal protection operates through preventive mechanisms, including public socialization and routine surveillance, alongside repressive measures like product confiscation and strict law enforcement. However, systemic effectiveness remains fundamentally constrained by consumers' inadequate legal awareness and the complex dynamics of online distribution networks. Ultimately, this current study concludes that fortifying public legal literacy and substantially augmenting institutional supervisory capacities constitute indispensable strategic imperatives for actualizing optimal, sustainable consumer protection against hazardous, unregulated commodities within the contemporary Indonesian domestic retail marketplace.